2017
DOI: 10.1055/s-0037-1601382
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Blood Loss Measurement during Cesarean Delivery

Abstract: Objective This study aims to compare the accuracy of visual, quantitative gravimetric, and colorimetric methods used to determine blood loss during cesarean delivery procedures employing a hemoglobin extraction assay as the reference standard. Study Design In 50 patients having cesarean deliveries blood loss determined by assays of hemoglobin content on surgical sponges and in suction canisters was compared with obstetricians' visual estimates, a quantitative gravimetric method, and the blood loss determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
1
47
0
1
Order By: Relevance
“…This is similar to the findings by Doctorvaladan et al who compared a hemoglobin content assay with visual, gravimetric, and colorimetric blood loss during 50 CDs. 16 This study found that the visual EBL correlated better with the hemoglobin assay than the gravimetric measured blood loss. Our study supports the findings of these authors and further suggests EBL has a higher sensitivity and specificity for predicting postpartum blood product transfusion than qBL, raising concerns that implementation of qBL may increase the rate of PPH and unnecessary transfusions.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This is similar to the findings by Doctorvaladan et al who compared a hemoglobin content assay with visual, gravimetric, and colorimetric blood loss during 50 CDs. 16 This study found that the visual EBL correlated better with the hemoglobin assay than the gravimetric measured blood loss. Our study supports the findings of these authors and further suggests EBL has a higher sensitivity and specificity for predicting postpartum blood product transfusion than qBL, raising concerns that implementation of qBL may increase the rate of PPH and unnecessary transfusions.…”
Section: Discussionmentioning
confidence: 66%
“…This unique aspect of the current study differentiates it from previously published studies on EBL and qBL. 16,17 Hamm et al compared EBL and qBL in all deliveries, regardless of mode of delivery or amount of blood loss, to predict a change in hemoglobin and also concluded that qBL does not predict a change in hemoglobin more accurately than EBL. Hamm et al examined a subgroup of women in this study with PPH (defined by ACOG revitalize, >1,000 mL regardless of mode of delivery).…”
Section: Discussionmentioning
confidence: 99%
“…31 Colorimetric image analysis is another option that is relatively new but in studies appears superior to both visual EBL and quantified blood loss in cesarean birth. 32,33…”
Section: Timing Of Placenta Removalmentioning
confidence: 99%
“…Lilley et al 22 concluded that in a mixed group of vaginal and cesarean deliveries, gravimetric assessment of blood loss during PPH was effective, while Johar and Smith 21 determined that in surgical procedures, the technique was frequently inaccurate due to issues such as recording bias, amniotic fluid/saline corruption, and human error. The presence of amniotic fluid in canisters and on soiled sponges was also shown to confound this method as described by Doctorvaladan et al 26 In practice, the quantitative gravimetric method has proven cumbersome and adoption has been poor. 21,22,34 The formula used to predict postoperative hemoglobin is logical and was consistently applied but does not account for the changes in blood volume as discussed earlier.…”
Section: Commentmentioning
confidence: 99%
“…The performance of the device has been validated in bench-top and clinical settings. [23][24][25][26][27] Accurate blood loss measurements using the novel device are known to be a better predictor of postoperative hemoglobin levels than visually estimated blood loss in patients having burn and other wound excisions. 28 While recognizing the limits of the hemoglobin concentration to guide transfusion decisions, we hypothesized that accurate blood loss determinations could improve the prediction of postoperative hemoglobin levels in cesarean delivery patients potentially leading to improved transfusion practice and overall patient management.…”
mentioning
confidence: 99%